1991
DOI: 10.1287/isre.2.3.192
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Instrument to Measure the Perceptions of Adopting an Information Technology Innovation

Abstract: This paper reports on the development of an instrument designed to measure the various perceptions that an individual may have of adopting an information technology (IT) innovation. This instrument is intended to be a tool for the study of the initial adoption and eventual diffusion of IT innovations within organizations. While the adoption of information technologies by individuals and organizations has been an area of substantial research interest since the early days of computerization, research efforts to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

96
4,470
9
200

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 6,448 publications
(5,366 citation statements)
references
References 36 publications
96
4,470
9
200
Order By: Relevance
“…Venkatesh et al (2003) suggested that social influence is important at the early stages of technology experience, with the effect diminishing over time. Our results are different from those of previous research (e.g., Moore & Benbasat, 1991;Venkatesh & Davis, 2000;AbuShanab & Pearson, 2007;Martins et al, 2014), because our sampling targets are experienced users. Researchers have indicated that people emphasize on various benefits when using a VC to search for cosmetic products (e.g., Athiyaman, 2002;Dholakia, Bagozzi, & Pearo, 2004).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Venkatesh et al (2003) suggested that social influence is important at the early stages of technology experience, with the effect diminishing over time. Our results are different from those of previous research (e.g., Moore & Benbasat, 1991;Venkatesh & Davis, 2000;AbuShanab & Pearson, 2007;Martins et al, 2014), because our sampling targets are experienced users. Researchers have indicated that people emphasize on various benefits when using a VC to search for cosmetic products (e.g., Athiyaman, 2002;Dholakia, Bagozzi, & Pearo, 2004).…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, previous researchers found that social influence positively affects behavioral intention to use new technology (e.g., Moore & Benbasat, 1991;Venkatesh & Davis, 2000;AbuShanab & Pearson, 2007;Martins et al, 2014). However, the influencing effects of social influence on VC re-usage intention are negative in our study.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…Most of the studies declare that relative advantages and compatibility increase the application of the information technology [10]. The concept of relative advantages is similar to perceived usefulness [19], and the concept of complexity is similar to perceived ease of use [20]. Thus, whether in technologies or services of the distance-based ETC system, the eTag system is regarded as a kind of transportation innovation in Taiwan.…”
Section: Research Hypothesesmentioning
confidence: 99%
“…In order to enhance the conceptual validity of the instrument, a two-step Q-sorting was adopted, as proposed by Moore and Benbasat [1991]. This served to verify content and convergent validity of measures.…”
Section: Survey Development and Analysismentioning
confidence: 99%